Exact Solution of Schrödinger Equation with Inverted Woods-Saxon and Manning-Rosen Potentials - Ikot, A. N.; Akpabio, L. E.; Umoren, E. B. (Journal of Scientific Research, 2010)
We have analytically solved the radial Schrödinger equation with inverted Woods-Saxon and Manning-Rosen Potentials. With the ansatz for the wave function, we obtain the generalized wave function and the negative energy spectrum for the system. Keywords: Inverted Woods-Saxon Potentials; Manning-Rosen Potential; Schrödinger Equation. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.5310 J. Sci. Res. 3 (1), 25-33 (2011)